HUBUNGAN FIQH DAN ILMU EKONOMI DALAM EKONOMI ISLAM - Joni, Yefri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2011)
Discussion about epistemology of Islamic economy among the Islam theologian is a very interesting discussion, remind that rules in life, which is known as fiqh, it cannot be directly regarded as an economic science. Likewise direct economic science cannot be labeled with Islamic’s name, because it source is different.